1983
DOI: 10.1038/ki.1983.98
|View full text |Cite
|
Sign up to set email alerts
|

Hydronephrosis: A new method to visualize vas afferens, efferens, and glomerular network

Abstract: We have developed a new preparation for in vivo visualization of the glomerular microcirculation, the vas afferens and the vas efferens. This preparation utilizes postischemic hydronephrosis (PIH) to destroy the renal tubular system while preserving a portion of the cortex. In this preparation, glomeruli and associated vasculature remained intact. Observations can be made with either incident light or transillumination. The inner diameter of the vas afferens, measured within 50 microns of the glomerular vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(79 citation statements)
references
References 29 publications
1
78
0
Order By: Relevance
“…To achieve this aim, we made use of the technique of renal hydronephrosis. This approach overcomes the difficulty of visualizing structures deep in the renal cortex by eliminating much of the renal medulla and rendering the remaining cortex transparent, while maintaining glomerular perfusion (25). Direct visualization of glomeruli in these experiments has demonstrated that leukocyte recruitment to the glomerulus occurs via a novel pathway involving overlapping roles for the ␤ 2 -integrin/ICAM-1 pathway, P-selectin, and platelets in the absence of detectable rolling in glomerular capillaries.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…To achieve this aim, we made use of the technique of renal hydronephrosis. This approach overcomes the difficulty of visualizing structures deep in the renal cortex by eliminating much of the renal medulla and rendering the remaining cortex transparent, while maintaining glomerular perfusion (25). Direct visualization of glomeruli in these experiments has demonstrated that leukocyte recruitment to the glomerulus occurs via a novel pathway involving overlapping roles for the ␤ 2 -integrin/ICAM-1 pathway, P-selectin, and platelets in the absence of detectable rolling in glomerular capillaries.…”
mentioning
confidence: 91%
“…To visualize the glomerular microvasculature, we used the technique of hydronephrosis (13,25,48,49). Given the possibility that the process of hydronephrosis may have impacted upon glomerular function, we examined various parameters to assess the inflammatory response in glomeruli of hydronephrotic kidneys.…”
Section: Figure 10mentioning
confidence: 99%
“…The techniques for induction of hydronephrosis and preparation of the hydronephrotic kidney have been described in detail previously [20,21]. In brief, after anaesthesia with halothane (Fluothane, Zeneca, Destelbergen, Belgium) a unilateral hydronephrosis was induced by a permanent ligation of the left ureter.…”
Section: Methodsmentioning
confidence: 99%
“…The right ureter was exposed by a small abdominal incision and ligated under ether anesthesia (Showa Chemicals, Tokyo, Japan). 8-10 wk after the surgery, renal tubular atrophy had progressed to a stage that allowed direct microscopic visualization of renal microvessels (20). At this point, the kidneys were excised and studied.…”
Section: Methodsmentioning
confidence: 99%